2015
DOI: 10.1007/s40472-014-0041-6
|View full text |Cite
|
Sign up to set email alerts
|

Early Clinical Results Using Normothermic Machine Liver Preservation

Abstract: The ongoing shortage of donor organs for liver transplantation results in high mortality rates for those on the waiting list. This has triggered considerable interest in the use of marginal liver grafts to increase the donor pool. Unfortunately, marginal grafts poorly tolerate preservation by cold storage (CS), resulting in an increased risk of liver injury and poor graft function after transplantation. Better preservation techniques are needed to fully utilize marginal grafts and to expand the number of organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…SNEVLP offers a unique opportunity as a protective strategy against preservation/reperfusion injury before liver transplantation. The advantages of warm machine perfusion over conventional CS have been reviewed extensively before . Future protective strategies might include deliveries of radical scavenging molecules (eg, N ‐acetylcysteine or tocopherol), or protective enzymes like hemoxigenase‐1, or H 2 S during SNEVLP .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SNEVLP offers a unique opportunity as a protective strategy against preservation/reperfusion injury before liver transplantation. The advantages of warm machine perfusion over conventional CS have been reviewed extensively before . Future protective strategies might include deliveries of radical scavenging molecules (eg, N ‐acetylcysteine or tocopherol), or protective enzymes like hemoxigenase‐1, or H 2 S during SNEVLP .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has focused mostly on improving liver preservation of marginal grafts. We and others have demonstrated that (sub)normothermic ex vivo liver perfusion reduces liver and bile duct injury in grafts harvested by donation after cardiac death (DCD) and fatty livers . Improving organ preservation in marginal grafts has the potential to increase the donor pool and improve graft function after liver transplantation.…”
mentioning
confidence: 99%